Gastric‐type duodenal neoplasms with rapid growth: A report of two cases. Issue 1 (23rd December 2022) - Sawada, Rikimaru; Kimoto, Yoshiaki; Furuta, Koichi; Nagae, Shinya; Ito, Yohei; Takeuchi, Nao; Takayanagi, Shunya; Kano, Yuki; Ishii, Rindo; Sakuno, Takashi; Negishi, Ryoju; Ono, Kohei; et al.
Abstract: While duodenal neoplasms of the gastric phenotype are uncommon and their natural history is unknown, gastric neoplasms of gastric phenotype reportedly grow rapidly and can invade the submucosa. Several studies suggest that duodenal neoplasms of gastric phenotype might have a high risk of deep invasion and lymph node metastasis. Duodenal neoplasms of gastric phenotype might also have a high biological malignancy and likely require early treatment if detected. Here, we report two cases of intramucosal duodenal carcinoma with a gastric phenotype that grew rapidly but was successfully resected endoscopically.